1996
DOI: 10.1007/s003359900090
|View full text |Cite
|
Sign up to set email alerts
|

Red coat color in Holstein cattle is associated with a deletion in the MSHR gene

Abstract: In mammals, red/yellow and brown/black colorations are determined by the distribution of two pigments, phaeomelanin and eumelanin, respectively, the relative amounts of which are controlled primarily by two loci, extension and agouti. Dominant alleles at the extension locus increase brown/black pigmentation, while recessive alleles block eumelanin synthesis, thereby extending red/ yellow pigmentation within the hair follicle melanocyte. Robbins and associates (1993) have shown that the pigmentation phenotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
66
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(70 citation statements)
references
References 5 publications
3
66
0
1
Order By: Relevance
“…Many of these mutations that are not confined to transmembrane regions are either associated with a premature stop codon, as is the case for dogs and cattle (Joerg et al. 1996; Newton et al. 2000), or a frameshift mutation as in yellow recessive mice (Robbins et al.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these mutations that are not confined to transmembrane regions are either associated with a premature stop codon, as is the case for dogs and cattle (Joerg et al. 1996; Newton et al. 2000), or a frameshift mutation as in yellow recessive mice (Robbins et al.…”
Section: Discussionmentioning
confidence: 99%
“…Gain-of-function and loss-of-function mutations of the MC1R gene determining dominant or partially dominant black/dark and recessive or partially recessive red/yellow/pale coat colour phenotypes, respectively, have been described in a large number of mammals including, for example, mice (Robbins et al, 1993), humans (Valverde et al, 1995) and several farm animals like cattle (Klungland et al, 1995;Joerg et al, 1996;Rouzaud et al, 2000), pigs (Kijas et al, 1998 and, horses (Marklund et al, 1996), dogs (Everts et al, 2000;Newton et al, 2000), cats (Eizirik et al, 2003;Peterschmitt et al, 2009), rabbits (Fontanesi et al, 2006) and goats (Fontanesi et al, 2009a). In sheep, classical genetic studies have identified two alleles at the Extension locus: the dominant black (E D ) allele caused by two missense mutations in the MC1R gene (p.M73K and p.D121N) and present in the Norwegian Dala, Corriedale, Damara, Black Merino, Black Castellana and Karakul breeds (Vå ge et al, 1999 andRoyo et al, 2008); and the wild type (E 1 ) allele widely distributed in most breeds (Searle, 1968;Sponenberg, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Expressed on cutaneous melanocytes [3], MC1R is a seven transmembrane domain G protein-coupled receptor of 317 amino acids belonging to the melanocotin receptor subfamily and has high binding affinity for MSH and ACTH [8,9]. In addition, some other studies show that MC1R variants are associated with the coat colors in cattle [10], [11], fox [12], and horse [13].…”
Section: Introductionmentioning
confidence: 99%